Effect of ephedrine on rapid intubation and haemodynamics using propofol and rocuronium: A randomized controlled trial - Alim, SM Abdul; Hossain, Md Mozaffer; Khatun, UH Shahera (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Ephedrine is a suitable drug to increase the cardiac output and tissue perfusion, in adequate dose, resulting in faster delivery of drug to muscles. This study was designed to compare the effect of pretreatment with ephedrine 75,100, 150 ?g/kg and saline on intubating conditions and haemodynamics during rapid tracheal intubation using propofol and rocuronium. The aim of this study was to evaluate the effects of different doses of ephedrine, given before induction, on intubating conditions and haemodynamics during rapid tracheal intubation. One hundred and twenty adult patients randomized into one of the four groups- I, II, III and IV were received iv ephedrine 75, 100, 150?g/kg and saline 0.9% (5ml) respectively, one minutes before administering propofol 2.5 mg/kg and rocuronium 0.6 mg/kg. Patients mean arterial pressure, heart rate, were recorded before induction (base line), just before intubation, and 1, 3, and 5 minutes after tracheal intubation. Data were analysed between the groups and within the groups using ANOVA test and X2-test. A p-value of <0.05 were considered as significant. Patients characteristics, baseline heart rate, and mean arterial pressure were comparable between the groups. Iutubating conditions were significantly better in group II (p=0.002). Pulse rate at different times were statistically significant (p<0.001) except base line and just before intubation. The mean difference of average mean blood pressure at different times were statistically significant (p<0.05) except baseline. In conclusion, pre-treatment with ephedrine 100 ?gm/kg improved the intubating conditions during rapid tracheal intubation using propofol and rocuronium. DOI: http://dx.doi.org/10.3329/jbsa.v22i1.18096 Journal of BSA, 2009; 22(1): 16-20